2012
DOI: 10.1142/s0217984912500959
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Impulse Breakdown Characteristics and Electrodynamic Process of Insulating Vegetable Oil-Based Nanofluid

Abstract: Insulating vegetable oils are considered environment-friendly and fire-resistant substitutes for insulating mineral oils. This paper presents the lightning impulse breakdown characteristic of insulating vegetable oil and insulating vegetable oil-based nanofluids. It indicates that Fe 3 O 4 nanoparticles can increase the negative lightning impulse breakdown voltages of insulating vegetable oil by 11.8% and positive lightning impulse breakdown voltages by 37.4%. The propagation velocity of streamer is reduced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…For positive lightning-impulse, nanoparticles in nanofluids will weaken the field strength and extremely increase positive breakdown voltages. However, the effect is inconspicuous for negative lightning-impulse [4]. Our results point out an opposite tendency with the breakdown behavior that has been observed in mineral oil-based nanofluids [1,8].…”
Section: Breakdown Voltage Of Nanofluidscontrasting
confidence: 74%
See 1 more Smart Citation
“…For positive lightning-impulse, nanoparticles in nanofluids will weaken the field strength and extremely increase positive breakdown voltages. However, the effect is inconspicuous for negative lightning-impulse [4]. Our results point out an opposite tendency with the breakdown behavior that has been observed in mineral oil-based nanofluids [1,8].…”
Section: Breakdown Voltage Of Nanofluidscontrasting
confidence: 74%
“…Recent research works have shown that conductive and semiconductive nanoparticles can be dispersed in mineral and vegetable insulating oils to enhance dielectric strength or thermal conductivity of the insulating oils. Magnetic Fe 3 O 4 nanoparticles have been proved of increasing the AC breakdown voltage of insulating oils for the case that the nanoparticles were well dispersed in oil [1][2][3][4][5]. It is also documented that both mineral and vegetable insulating oils are possible to show enhanced AC breakdown voltages and partial-discharge-inception voltages after the oils are modified by semiconductive TiO 2 nanoparticles [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in positive impulse breakdown voltage of the nano-oil was larger than the negative one. This phenomenon can be explained by space charge theory [23,29]. In the positive polarity model (Figure 11), some electrons near the positive-electrode were captured by nanoparticles.…”
Section: Lightning Impulse Breakdown Voltagementioning
confidence: 93%
“…Compared with mineral oil, vegetable insulating oil has a higher AC and DC breakdown voltage [22]. The addition of a certain amount of magnetic conductive nanoparticles, Journal of Nanomaterials such as Fe 3 O 4 , to either vegetable insulating oil, improves its positive (∼37.4%) and negative (∼11.8%) lighting impulse breakdown voltages [23]. In addition, nanoparticles can form negatively charged particles in a short time period and consequently affect the development of the streamer.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [111] studied nanoparticles of Fe 3 O 4 with a modified surface by oleic acid suspended in vegetable oil (rapeseed oil). The average size of used nanoparticles was 30 nm in diameter.…”
Section: Nitrides and Other Nanoparticlesmentioning
confidence: 99%